FORMATION OF A CULTURE OF GENDER EQUALITY AMONG STUDENTS IN PHYSICAL EDUCATION CLASSES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Today, the issue of gender equality is gaining importance in all spheres of society, including the education system. One of the urgent tasks is to form a culture of gender equality for the comprehensive development of the growing younger generation, their ability to find their place in society and grow up as equal citizens. In particular, physical education classes provide unique opportunities for students to develop important qualities such as social skills, cooperation, mutual respect and equality, along with physical development. However, unfortunately, physical education classes in many educational institutions are still conducted under the influence of gender stereotypes. While strength-demanding exercises and sports are given more attention for boys, exercises that develop agility and flexibility are recommended for girls. Such an approach does not fully take into account the interests and abilities of students, artificially dividing them into gender roles. As a result, students may experience problems such as avoidance of physical activity, lack of self-confidence, and insufficient development of teamwork skills.